Application of Surfactant Micellar Solutions as Extractants and Mobile Phases for TLC-Determination of Purine Bases and Doping Agents in Biological Liquids - Yedamenko, Daria; Loginova, Lidia (Orbital: The Electronic Journal of Chemistry, 2015)
Separation of caffeine and its metabolites (theophylline and theobromine) and doping agents (spironolactone, propranolol, and ephedrine) and determination of caffeine in serum sample and propranolol and ephedrine in urine were studied on normal-phase thin layers (“Sorbfil-UV-254”). Aqueous organic solvents and aqueous micellar surfactant solutions were compared as the mobile phases for separation. The acceptable separation of purine bases and doping agents was achieved by micellar Thin Layer Chromatography and normal-phase Thin Layer Chromatography. Anionic surfactant solution with added 1-propanol was the best eluent as for caffeine, theophylline, and theobromine separation, as for doping agents. The best characteristics of caffeine extraction from serum, and propranolol and ephedrine from urine were achieved when micellar eluent based on non-ionic Tween-80 surfactant was used. DOI: http://dx.doi.org/10.17807/orbital.v7i1.632